Community-based tourism in practice: evidence from three coastal communities in Bohuslän, Sweden - Lindström, Kristina N.; Larson, Mia (Bulletin of Geography. Socio-economic Series, 2016)
Local involvement in tourism development is defined as a key issue for sustainable tourism, however it is often questioned and less seldom implemented in reality. Reasons behind this condition are lack of knowledge and practical experience on community-based tourism as a bottom-up approach. In this paper it is argued that local involvement in tourism development is both a democratic right and a strategic destination management tool. The paper scrutinizes a process of collaboration and local participation in a tourism development project within three coastal communities on the Swedish West Coast. A mixed-methods approach was employed in the project with the specific aim of investigating attitudes to the community and tourism development and of involving community stakeholders in exploring alternative avenues of tourism development. The article describes four phases of the process of local involvement in a tourism development project: step 1, formation of a representative project group and negotiation of community-based approach; step 2, consulting local stakeholders and employing a mixed-methods approach; step 3, elaborating results with local stakeholders; step 4, increased community collaboration.